Antifungal resistance of candida species isolated from HIV patients in a tertiary care hospital, Mysuru, Karnataka - Umamaheshwari Shivaswamy; M N Sumana (Wolters Kluwer Medknow Publications, 2020)
Context: Candidiasis still remains as a common opportunistic infection in patients with human immunodeficiency virus (HIV). Drug resistance has become a serious health concern because of indiscriminate usage and dosage. Aim: To determine the antifungal resistance pattern of Candida albicans and non-albicans Candida (NAC) from HIV patients. Subjects and Methods: The study was carried out in the department of microbiology at a tertiary care hospital. Candida isolates obtained from HIV patients were tested for drug susceptibility by Vitek-2 automated system. Results: Antifungal susceptibility pattern (n=109) revealed that 15% of the isolates were resistant to at-least one and 85% were sensitive to all the drugs tested. About 10% and 19% of C. albicans showed resistance to fluconazole and flucytosine respectively. Among non-albicans tested, only C. tropicalis (14%) exhibited resistance to flucytosine. Conclusions: Knowledge on epidemiology, species prevalence, and drug resistance pattern may guide for effective therapy. This reduces morbidity and also improves the quality of life.